2011
DOI: 10.1016/j.exger.2010.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and mobility decline in older persons

Abstract: We examined whether adherence to a Mediterranean-style diet has positive effects on mobility assessed over a nine-year follow-up in a representative sample of older adults. This research is part of the InCHIANTI Study, a prospective population-based study of older persons in Tuscany, Italy. The sample for this analysis included 935 women and men aged 65 years and older. Adherence to the Mediterranean diet was assessed at baseline by the standard 10-unit Mediterranean diet score (MDS). Lower extremity function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 35 publications
(32 reference statements)
3
117
0
6
Order By: Relevance
“…Physical activity was dichotomized between inactive, low, and moderate to high. 25 Trained physiotherapists performed a physical assessment of muscle strength, gait, and balance. Lower extremity function was determined using the Short Physical Performance Battery (SPPB).…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was dichotomized between inactive, low, and moderate to high. 25 Trained physiotherapists performed a physical assessment of muscle strength, gait, and balance. Lower extremity function was determined using the Short Physical Performance Battery (SPPB).…”
Section: Methodsmentioning
confidence: 99%
“…However, four fulltext articles were duplicate publications: two studies were reported on four occasions in separate articles [73][74][75][76]. Therefore a total of 12 studies were included in this narrative review (see Table 1).…”
Section: Adherence To the Mediterranean Diet Physical Frailty And Samentioning
confidence: 99%
“…In a separate analysis of the InCHIANTI study [88] Milaneschi et al [73] reported that participants with higher adherence to a MedDiet (defined as MDS score ≥ 6) were less likely to have mobility disability at baseline (defined as SPPB score <10) even after adjustments for age, gender, energy intake, BMI, MMSE score, physical activity, instrumental activities of daily living, depressive symptoms, number of chronic diseases and medications (OR = 0.50; 95% CI: 0.30-0.82; p = 0.006). Milaneschi et al [73] further reported that participants with greater adherence to a MedDiet experienced significantly less decline in SPPB scores over time (3-year follow-up: 0.9 points higher (SE = 0.2, p ≤ 0.001); 6-year follow-up: 1.1 points higher (SE = 0.3, p = 0.0002); 9-year follow-up: 0.9 points higher (SE = 0.4, p = 0.03)). Using two dietary assessment instruments (MDS and MEDAS) León-Muñoz et al [74] reported that over a mean follow-up period of 3.5 years, an increasing adherence to a MedDiet was associated with decreasing risk of physical frailty.…”
Section: Adherence To a Mediterranean Diet And Physical Frailtymentioning
confidence: 99%
See 1 more Smart Citation
“…• Walking distance: 2.4 m (Guralnik et al, 1995;Ostir et al, 1998;Shumway-Cook et al, 2003;ShumwayCook et al, 2002), 4 m (Bean et al, 2011;Milaneschi et al, 2010Milaneschi et al, , 2011Patel et al, 2006;Sayers et al, 2006), not specified (Reid et al, 2008; • Score range: 0-12 (Bean et al, 2011;Sayers et al, 2006;Shumway-Cook et al, 2003) or 1-11 (Ostir et al, 1998) • 0-4: severe mobility limitation, 5-9: mild to moderate mobility limitation, and 10-12: good mobility (Milaneschi et al, 2010) • Poor mobility performance ≤ 10 (Milaneschi et al, 2011) • Moderate mobility impairment > 7; severe mobility impairments ≤ 7 (Reid et al, 2008) Carried out in the home by trained interviewers (Guralnik et al, 1995) review demonstrates that there are various mobility assessment tools. These instruments have fallen into two broad categories: selfreport and performance-based measures.…”
Section: Climbingmentioning
confidence: 99%